Caregiver satisfaction with interim silver diamine fluoride applications for their children with caries prior to operating room treatment or sedation. (16th August 2019) - Cernigliaro, Dana; Kumar, Anjali; Northridge, Mary E.; Wu, Yinxiang; Troxel, Andrea B.; Cunha‐Cruz, Joana; Balzer, Jay; Okuji, David M.
Abstract: Objective: To ascertain caregiver satisfaction with silver diamine fluoride (SDF) application(s) as an intermediate care path for their children with caries. Methods: Caregivers were recruited at two community health centers when they arrived for a previously scheduled operating room/sedation appointment for their children with caries who had previously been treated with SDF. They were asked to complete a survey regarding their satisfaction with SDF treatment while they waited during their children's dental treatment. Results: Caregivers overwhelmingly reported that they were satisfied with SDF treatment (81.3%), and that the black mark was not an issue for their children (91.7%) or themselves (87.5%). Moreover, their perception of their children's oral health quality of life was high. Conclusions: By arresting caries, SDF offers an intermediate care path for pediatric patients for whom OR/sedation treatment was not immediately available. Moreover, most caregivers were satisfied with SDF treatment for their children.